2002
DOI: 10.1039/b110705d
|View full text |Cite
|
Sign up to set email alerts
|

Electropolymerization of 2-methoxyaniline. Polymerization kinetics and phenazine insertion at low monomer concentrationElectronic supplementary information (ESI) available: Cyclic voltammograms. See http://www.rsc.org/suppdata/cp/b1/b110705d/

Abstract: The electropolymerization of 2-methoxyaniline (MOA) has been found to yield products having structure and properties dependent on the monomer concentration, with the insertion of phenazinic units giving a redox-type polymer at low concentrations. The kinetics of this process is studied in 1 M HClO 4 solutions containing different monomer concentrations. The voltammetric results are compared with the electropolymerization, in similar experimental conditions, of other aryl amines such as aniline and 2-methylanil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…4(c)). The potentials of these two redox couples are reasonably consistent with previous reports for POMA electrodeposited under acidic conditions, although some of those films exhibited additional peaks at more positive potentials [29,[32][33][34][35][36][37]. We are currently extending our investigations of the chemical and electrochemical properties of POMA formed under these high-pH solution conditions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…4(c)). The potentials of these two redox couples are reasonably consistent with previous reports for POMA electrodeposited under acidic conditions, although some of those films exhibited additional peaks at more positive potentials [29,[32][33][34][35][36][37]. We are currently extending our investigations of the chemical and electrochemical properties of POMA formed under these high-pH solution conditions.…”
Section: Discussionsupporting
confidence: 88%
“…The electrodeposition and characterization of POMA films was previously reported [29][30][31][32][33][34][35][36][37], but to our knowledge this is the first reported example of an electroactive POMA film electrodeposited from such high pH conditions. Poly(aniline) has been more extensively studied, and previous studies have demonstrated that PANI films can be electrodeposited from electrolytes over a wide pH range [38].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 8 shows that there are remarkable differences. Thus, the PoMea produced from Magh-Cu is electroactive; however, no redox processes are observed for the same polymer from PoMea/Magh-H. For PoMea/Magh-Cu, a broad anodic peak at 0.72 V appears and two reduction peaks (at 0.44 V and around 0.6 V) are observed in the reverse scan, which suggest the existence of two redox processes as occurs in most ring-substituted polyaniline [34][35][36][37].…”
Section: Resultsmentioning
confidence: 94%
“…To overcome that, polymers of derivatives such as 2-methylaniline [24][25][26][27], 2-ethylaniline [28] or 2-methoxyaniline (MOA) [29][30][31][32][33] have been investigated, and also copolymers or composites [34] of aniline (ANI) and other suitable monomers [35][36][37]. A copolymer which is gaining increasing attention is poly(aniline-co-2-methoxyaniline) (PAcoM) [38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%